Regional Patterns of Deindustrialization and Prospects for Reindustrialization in South and Central East European Countries - Zoran Aralica; Nebojsa Stojcic (The Vienna Institute for International Economic Studies (wiiw), 2015)
Past decades in Central and South East European countries have been characterised with shrinking of manufacturing output and employment. However, little is known about the causes, nature and the extent of deindustrialization in these countries at the regional level. The objective of this research is to explore the regional patterns of deindustrialization and determinants of reindustrialization in several CEECs and SEECs. Our analysis presents one of the first attempts to address these processes at regional level while taking into account the spatial effects. A spatial panel Durbin econometric technique is applied to data covering 2006 – 2012 period to discern inter – regional from intra – regional effects. Results of investigation reveal spatial clustering of economic activity. Traits of deindustrialization are observed in metropolitan areas and in regions on eastern belt of these countries while other regions reveal traits of shift towards high technology intensive manufacturing. Recommendations for future policy makers are provided.
Keywords: 330; deindustrialization; reindustrialization; regions; spatial analysis